Enzymatic activity of amylase and acid phosphatase in the soil-plant system (Research, Society and Development, 2025)
Bioindicators, also known as biological indicators, are vital tools for assessing soil quality. They act effectively, helping to mitigate negative impacts on soil biota. This study's main objective was to highlight the enzymatic activity of amylases and acid phosphatases in soil, investigating and clarifying their crucial role. The methodology employed was a quantitative integrative review, with searches conducted in the Google Scholar and SciELO databases. Studies published between 2020 and 2025, in Portuguese and English, were considered. Understanding the activity of these enzymes is crucial. Amylase, for example, is notable for its high resistance to adverse conditions such as high salt concentrations, pH and temperature variations, and the presence of organic solvents. It exhibits excellent stability and efficient catalytic activity, being grouped into α-amylase and β-amylase, which differ primarily in starch synthesis. Phosphatases, in turn, are responsible for catalyzing the hydrolysis of phosphoric acid esters and anhydrides. They can be subdivided into acid and alkaline phosphatases, distinguished by their pH. Acid phosphatases are the most studied, especially in Brazil, given the typically acidic nature of the country's soils. In short, knowledge of enzymatic activity enables more informed soil management decisions. These enzymes make excellent contributions to managing reaction rates and promote the enrichment of organic matter, playing an essential role in soil function.